KATEGORIE „AUTORSTWA” I „UTWORU” W PROJEKCIE EUROPEJSKIEGO KODEKSU PRAWA AUTORSKIEGO - Konach, Teodora (Zeszyty Prawnicze, 2016)
THE CATEGORIES OF “AUTHORSHIP” AND “THE WORK” IN THE DRAFT FOR THE EUROPEAN COPYRIGHT CODE Summary Economic and technological factors have brought radical changes to the legal framework of authors’ copyright protection on both the national and international levels. Despite twenty years of directives and ECJ case law, the copyright system in the European Union is still fragmented and ill-adapted. This paper provides an insight into the Wittem Group’s European Copyright Code, established in 2002, the first draft European copyright codification. The aim of the Wittem Copyright Code is to increase the overall protection of authors and to provide a new, holistic approach to copyright. The paper presents useful clarification of the meaning of specific provisions in the European Copyright Code, and particularly of the concepts of “The Work” and “Authorship”.